Microbial adaptation to the healthy and inflamed gut environments. Issue 1 (9th November 2020) - Guo, Yijie; Kitamoto, Sho; Kamada, Nobuhiko
ABSTRACT: There are 100 trillion diverse bacterial residents in the mammalian gut. Commensal bacterial species/strains cooperate and compete with each other to establish a well-balanced community, crucial for the maintenance of host health. Pathogenic bacteria hijack cooperative mechanisms or use strategies to evade competitive mechanisms to establish infection. Moreover, pathogenic bacteria cause marked environmental changes in the gut, such as the induction of inflammation, which fosters the selective growth of pathogens. In this review, we summarize the latest findings concerning the mechanisms by which commensal bacterial species/strains colonize the gut through cooperative or competitive behaviors. We also review the mechanisms by which pathogenic bacteria adapt to the inflamed gut and thrive at the expense of commensal bacteria. The understanding of bacterial adaptation to the healthy and the inflamed gut may provide new bacteria-targeted therapeutic approaches that selectively promote the expansion of beneficial commensal bacteria or limit the growth of pathogenic bacteria.